Editorial: Screen time, social media and developing brains: a cause for good or corrupting young minds?. Issue 3 (18th August 2019) - Dubicka, Bernadka; Martin, Jennifer; Firth, Joseph
Abstract : In 2018, the Royal College of Psychiatrists held a debate for young people about social media, a subject of their own choosing. The young people spoke eloquently but had differing views. One young person held up his smartphone and stated 'this is my heroin – it's the heroin of our generation'. In contrast, another young person argued 'I don't agree – this is my life line, I am a looked‐after child, living on my own, and it's the only way I have of keeping in touch with my family and friends'.